Faktor-Faktor yang Mempengaruhi Kesejahteraan Psikologis Orang Tua dengan Anak Berkebutuhan Khusus: Studi Literatur - Toni Nugraha Jamaluddin. HB Toni; Haerani Nur (Universitas Negeri Gorontalo, 2025)
This study aims to identify and analyze the factors influencing the psychological well-being of parents with children with special needs. It provides a theoretical basis for developing psychological support interventions for parents. The research method used was a literature review (library research) with thematic content analysis of 30 selected national and international articles. Articles were selected based on their relevance to the topic of psychological well-being and children with special needs. The results showed that internal factors influencing psychological well-being include resilience, self-adjustment, gratitude, self-control, stress coping, optimism, self-acceptance, parenting self-efficacy, and adversity quotient. External factors include family support, social support, quality of life, economic conditions, marital relationship quality, and social environment. The conclusion of this study is that the psychological well-being of parents of children with special needs is determined by the interaction of internal and external factors, which must both be considered to optimize psychological support efforts.